Pengaruh kualitas layanan dan kepercayaan nasabah terhadap loyalitas nasabah - Meliana Utami; Tati Handayani; Pusporini Pusporini (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This research was conducted to prove the influence of service quality and customer trust towards the customer loyalty of Islamic Banks in South Jakarta. This study uses population of Islamic banks’ customers in Jakarta with a sample of 100 respondents and questionnaire distribution techniques. The analytical tool used for this study is Partial Least Square 3.0 (PLS). The results of this study found that the service quality has a coefficient of 0.462 with t-count of 3.238 (> t-table 1.985) and a significant value of 0,000 (<0.05). These numbers show that the service quality has a significant effect on customer loyalty or in other words, H1 is accepted. For the second variable, customer trust shows a coefficient of 0.441, t-count of 3.123 (> t-table 1.985) and a significant value of 0,000 (<0.05). These numbers conclude that customer trust has a significant effect on customer loyalty or in other words, H2 is accepted.